The anatomical pattern and determinants of pain in the neck and upper limbs: an epidemiologic study. - Walker-Bone, K; Reading, I; Coggon, D; Cooper, C; Palmer, K (2004)
Little is known about the distribution and determinants of pain at multiple sites in the neck and upper limb. To investigate the prevalence, pattern, and clustering of such pains and the association of extensive involvement with putative risk factors, we mailed a questionnaire to a community sample of 9696 working-aged adults. Age-sex specific prevalence rates for pain were estimated and the frequency of bilateral involvement, pairwise overlap at different sites, and extent to which reports clustered within individuals were explored. Associations of multi-site involvement with age, gender, psychological health, smoking, and employment status were assessed by logistic regression. Among 6038 responders, 2657 reported at least a day of neck or upper limb pain in the past 7 days, including 1843 whose symptoms rendered normal activities difficult or impossible. Pain was frequently bilateral or in the dominant arm. Significant associations were seen for pain at anatomically adjacent sites. Pain affecting every site considered (neck, shoulders, elbows, wrists/hands) was far more common than might be expected if each site were statistically independent (observed/expected ratio 8750). Being female, unemployed, a blue-collar worker, or a smoker were independent risk factors for such extensive pain, but the strongest association was with psychological ill-health (odds ratio for worst vs. best third of the SF-36 low vitality score, 30.3, 95% CI 7.1-129.0). Neck and upper limb pain commonly cluster, and frequently display symmetry and adjacent patterns of involvement. Extensive neck and upper limb pain is far more strongly associated with poor mental vitality than localised pain.